Governance and interdependencies of critical infrastructures: Exploring mechanisms for cross-sector resilience. (October 2021) - Rydén Sonesson, Tove; Johansson, Jonas; Cedergren, Alexander
Highlights: Critical infrastructure setting in Sweden exhibit clear sectoral silo-boundaries. Information-sharing depends on personal relationships, trust and mutual needs. Interdependencies acknowledged, but processes and methods lacking. Resilience shaped by past events, compliance, contracts and sense of ownership. Financial and efficiency gains increase actor engagement and resilience investments. Abstract: Much contemporary critical infrastructure research has been devoted to studies of the effects of risks stemming from interdependencies between critical infrastructures, here referred to as  interdependency-related risks . However, this research has placed limited emphasis on infrastructure actors' efforts to manage such risks in practice, and it remains unclear to what extent and how critical infrastructure actors work to increase resilience related to interdependency-related risks. This paper explores mechanisms for addressing interdependency-related risks across three critical national infrastructure sectors in Sweden: transportation, energy and telecommunication. The paper combines a document study and an interview study, and nine mechanisms are identified: (1) Swedish critical infrastructures are subject to clear silo-structures, (2) dedicated individuals and personal relationships are central to existing cross-sector collaborations, (3) information-sharing occurs between sectors, including exchange of sensitive information, but is mainly based on trust or mutual information-needs, (4) while interdependencies are acknowledged, explicit and adequate methods and protocols for how to assess and manage interdependency-related risks seem to be scarce, (5) clear risk ownership, and a connection to physical interdependencies and the core business seems to influence the level of cross-sector engagement, (6) governance of interdependency-related risks is mostly reactive and heavily influenced by past events, (7) compliance have a potential for sparking collaboration, and finally, (8) customer demands in particular, and (9) economic factors in general, play an important role for incentivising cross-sector collaboration. Finally, the paper extensively discusses the implications of these findings and outlines the potential for future research directions to improve cross-sector resilience.